Адамның құндылық бағдары мәдениеттану мәселесі ретінде - Kabylbayeva, K. N.; Ismagambetova, Z. N. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The article is devoted to the problem that is on the agenda: the problem of formation of values and value orientations. The authors make an analysis of the concepts of “values” and “value orientation”, as well as the sources of their formation, the authors define the essence of value and value orientations in the social, philosophical and cultural sciences. The authors carry out a comparative analysis of various methodological approaches in the study of the problem of values. In the article authors define the main parameters of value orientations. The authors disclose characteristics of value orientations in human behavior. The authors consider the problem of values in cultural and anthropological dimension. The article poses the problem of substantiating the cultural anthropological approach in the study of the essence of values. The authors analyse modern aspects of theoretical and methodological approaches to the study of values. In the article authors consider essence of values, value orientations, reveal their role in the formation of human behavior, in social and cultural communication. They show the influence of culture on the formation of value orientations. In the article, the authors substantiate the need to study the problem of the formation of personal values in modern Kazakhstan society in the format of a cultural anthropological approach. This approach allows us to explore the influence of a system of values and value orientations on human behavior, on intercultural communication. Key words: culture, value, value orientations, national culture, family, work, education, youth, globalization, west, east, Kazakh, society, intercultural communication.